Umm so I'm confused
The question says
5x - 2y = 24
x + 2y = 12
1 answer:
Answer:
Step-by-step explanation:
5x-2y=24
x+2y=12
add the two equations
(5x-2y)+(x+2y)=24+12
6x=36
x=6
Plug in x=6 into any of the two equations
5(6)-2y=24
30-2y=24
-6= -2y
y= 3
x=6
y=3
(6,3)
You might be interested in
The Pythagorean theorem is a^2 + b^2 = c^2. You use it when solving for the sides of a triangle.
Answer:
I wish you luck
Step-by-step explanation:
Answer:
Step-by-step explanation:
term | Phrase
inequality | 63<8k
Expression | bc+1-(8d-4)
Equation | w^4=81
46/14. Hoped this helped!
Answer: 12:5
Step-by-step explanation: